The unity hypothesis revisited: can the male/female incongruent McGurk effect be disrupted by familiarization and priming? - Ma, Kennis S. T.; Schnupp, Jan W. H. (Frontiers in Psychology, 2023)
The unity assumption hypothesis contends that higher-level factors, such as a perceiver's belief and prior experience, modulate multisensory integration. The McGurk illusion exemplifies such integration. When a visual velar consonant /ga/ is dubbed with an auditory bilabial /ba/, listeners unify the discrepant signals with knowledge that open lips cannot produce /ba/ and a fusion percept / da/ is perceived. Previous research claimed to have falsified the unity assumption hypothesis by demonstrating the McGurk effect occurs even when a face is dubbed with a voice of the opposite sex, and thus violates expectations from prior experience. But perhaps stronger counter-evidence is needed to prevent perceptual unity than just an apparent incongruence between unfamiliar faces and voices. Here we investigated whether the McGurk illusion with male/female incongruent stimuli can be disrupted by familiarization and priming with an appropriate pairing of face and voice. In an online experiment, the susceptibility of participants to the McGurk illusion was tested with stimuli containing either a male or female face with a voice of incongruent gender. The number of times participants experienced a McGurk illusion was measured before and after a familiarization block, which familiarized them with the true pairings of face and voice. After familiarization and priming, the susceptibility to the McGurk effects decreased significantly on average. The findings support the notion that unity assumptions modulate intersensory bias, and confirm and extend previous studies using male/female incongruent McGurk stimuli.